Role of the G Protein-Coupled Receptor, mGlu1, in Melanoma Development - Janet Wangari-Talbot; James Goydos; Suzie Chen (MDPI AG, 2010)
Melanoma remains one of the cancers for which a decline in morbidity has not been achieved with current scientific and medical advances. Mono-therapies targeting melanoma have been largely ineffective, increasing the need for identification of new drugable targets. Multiple tumor suppressors and oncogenes that impart genetic predisposition to melanoma have been identified and are being studied in an attempt to provide insight on the development of anti-melanoma therapies. Metabotropic Glutamate Receptor I (GRM1) has recently been implicated as a novel oncogene involved in melanomagenesis. GRM1 (mGlu1, protein) belongs to the G protein coupled receptor (GPCR) super family and is normally functional in the central nervous system. Our group showed in a transgenic mouse model system that ectopic expression of Grm1 in melanocytes is sufficient to induce spontaneous melanoma development in vivo. GPCRs are some of the most important therapeutic drug targets discovered to date and they make up a significant proportion of existing therapies. This super family of transmembrane receptors has wide spread expression and interacts with a diverse array of ligands. Diverse physiological responses can be induced by stimulator(s) or suppressor(s) of GPCRs, which contributes to their attractiveness in existing and emerging therapies. GPCR targeting therapies are employed against a variety of human disorders including those of the central nervous system, cardiovascular, metabolic, urogenital and respiratory systems. In the current review, we will discuss how the identification of the oncogenic properties of GRM1 opens up new strategies for the design of potential novel therapies for the treatment of melanoma.